Factors influencing health-seeking behaviours of asylum seekers, refugees, and undocumented immigrants: A systematic review of peer-reviewed articles - Ahmadinia, Hamed; Eriksson-Backa, Kristina (Nordic Journal of Library and Information Studies, 2025)
This review investigates the impact of personal and contextual factors on health-seeking behaviours in terms of health-related information and healthcare service needs and utilization among asylum seekers, refugees, and undocumented immigrants using an adapted framework based on an extended Longo health information model. The 73 peer-reviewed records included in this systematic review were obtained from WoS, Ebsco, and Scopus. This review shows that culture, religion, policy, and systematic inequalities may play three different roles for our studied population, including facilitators, barriers, and health-related information sources. The findings indicated that providing universal health-related information and healthcare services may not meet all of the healthcare needs of our study population. As a result, healthcare providers must take a cross-cultural approach when designing, developing, and delivering specific health promotion programmes, treating patients with respect and attention, and providing health-related information and healthcare services based on ethnic, cultural, religious, and migration statuses.